Autonomous Weapon Systems and The Humanitarian Principle of Distinction - Gökhan Güneysu (Annales de la Faculté de Droit d’Istanbul)
Autonomous Weapon Systems have been on the international agenda for more than ten years now. Autonomy in warfare and its attached promises have been dubbed as the most recent revolution in military technologies. Many commentators have a rather sceptical view of these systems. They believe that the very existence of international humanitarian law and the minimal protection offered by it are at risk due to the gradually increasing use of autonomous weapons. Albeit a minority, some other commentators welcome the development of these warrior machines, with the insinuation that wars will be conducted more humanely due to the dehumanisation of warfare. This paper undertakes to evaluate these autonomous systems in terms of their compatibility with the requirements brought about by the principle of distinction, one of the cardinal principles of international humanitarian law.